Learning in COVID-19 Era, Responses of Students and Lectures - Dina Rafidiyah; Jamiatul Hamidah; Rahmatya Nurmeidina (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2021)
When the COVID-19 pandemic occurred, face-to-face classes at the University of Muhammadiyah Banjarmasin switched to the online method. Changing habits from direct learning to online learning requires adjustment and habituation, both for lecturers and students. This study aims to describe (1) the obstacles faced by Mathematics and Indonesian students in conducting online lectures; (2) online applications are used by mathematics and Indonesian language lecturers, including assessment procedures (attendance, assignments, and examinations); and (3) obtained solutions to overcome various obstacles to online learning so that learning objectives can be achieved. This research method is a descriptive research methodology. Data obtained through Google Form. The participants are 44 students and 10 lecturers. The results showed that student complaints against online learning were limited internet networks, limited quota, the large number of assignments given by lecturers, and a lack of understanding of the material presented by the lecturers. While the lecturer's strategy in assessing students online is carried out by combining several supporting media or applications. Some of the alternative solutions offered are (1) an agreement between lecturers and students on what methods and media to use in online lectures; (2) opening opportunities to communicate openly between lecturers and students to avoid misunderstanding of the material presented, assignments and so on; (3) the integration of media and applications according to the subjects being taught; and (4) the making of exam questions is more focused on students' understanding so as to minimize the possibility of students to cheat.